Propagation of liberalism by youths on social media - Juzlinda Mohd Ghazali; Norsaleha Mohd. Salleh; Helyawati Baharudin; Shafinaz Mohammad Niyaz Khan; Siti Noor Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2020)
Social media has been rooted in our society in that it is impossible, particularly for youths, to not be in any social media platform. Everyone gets frenzy when it comes to socializing online. They spend an average of 6-8 hours on the Internet per day. Thus, raises the fact of being exposed to varied contents including misleading ones. This study discloses the role of social media in propagating liberal thought among youths in Malaysia. Through observation, eleven influenced and liberal-inclined Facebook youths have been selected to be interviewed and five had agreed. Four Islamic scholars were also approached for their opinions and recommendations toward this issue. The finding shows that youths do play a significant role in influencing social media users’ thought. This study also exposed that liberal movement in Malaysia is well planned in its effort to propagate liberalism in Malaysia. Everyone from individuals to authorized bodies and government must do their part in curbing the spreading of liberalism.